1996
DOI: 10.1111/1523-1747.ep12345488
|View full text |Cite
|
Sign up to set email alerts
|

Localization of Human T-Cell Lymphotropic Virus-1 tax Proviral Sequences in Skin Biopsies of Patients with Mycosis Fungoides by in situ Polymerase Chain Reaction

Abstract: The histopathologic diagnosis of mycosis fungoides (MF), even when clinical manifestations of the disease seem convincing, is often tenuous. The observation that practically all patients with MF harbor human T cell lymphotropic virus type I (HTLV-I) proviral sequences in their circulating lymphocytes raised the possibility that such viral footprints could be detected in their cutaneous infiltrates. Application of in situ polymerase chain reaction (PCR) to skin biopsies of 11 of 12 patients demonstrated this as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…HTLV-1 is found in adult T-cell lymphoma and leukemia, and it has been implicated by several studies in CTCL (Zucker-Franklin and Pancake, 1994;Pancake et al, 1995;Khan et al, 1996). However, others have not been able to confirm these findings (Boni et al, 1996;Wood et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…HTLV-1 is found in adult T-cell lymphoma and leukemia, and it has been implicated by several studies in CTCL (Zucker-Franklin and Pancake, 1994;Pancake et al, 1995;Khan et al, 1996). However, others have not been able to confirm these findings (Boni et al, 1996;Wood et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…32 HTLV-1 is found in adult T-cell lymphoma and leukemia, and it has been implicated by several studies in CTCL. [33][34][35] Others have not been able to confirm this finding. 36,37 In this study, all except one of the patients with CTCL had negative HTLV-1 serology studies at baseline.…”
Section: Discussionmentioning
confidence: 99%
“…Most patients with CTCL are negative for antibodies to the structural proteins of HTLV-I, and thus a causative role for this virus is usually dismissed. However, numerous studies have found HTLV-I-related proviral tax sequence or deleted proviruses in tumor samples from CTCL patients [27][28][29][30][31][32][33][34]. Recently a study on the northeastern coast of Brazil found HTLV-I integrated proviral sequences by southern blot in several mycosis fungoides-like cutaneous lymphomas, and CD30 + largecell anaplastic lymphomas [35].…”
Section: Htlv-i-associated Cutaneous T-cell Lymphoma (Ctcl)mentioning
confidence: 99%